Estradiol and progesterone bioavailability for moderate to severe vasomotor symptom treatment and endometrial protection with the continuous-combined regimen of TX-001HR (oral estradiol and progesterone capsules). Issue 7 (July 2019) - Lobo, Rogerio A.; Liu, James; Stanczyk, Frank Z.; Constantine, Ginger D.; Pickar, James H.; Shadiack, Annette M.; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: In the REPLENISH trial, women receiving TX-001HR—an oral, softgel capsule, combining 17β-estradiol (E2) and progesterone (E2 mg/P4 mg 1/100, 0.5/100), had significantly improved vasomotor symptoms, while having their endometrium protected from hyperplasia. The objective here was to describe P4 levels sufficient to counteract the potential endometrial effects of 1 or 0.5 mg oral E2 with TX-001HR. Methods: In REPLENISH (phase 3; NCT01942668), serum P4, E2, and estrone (E1) levels were characterized in postmenopausal women treated with TX-001HR (E2 mg/P4 mg: 1/100, 0.5/100, [0.5/50, 0.25/50 and placebo not reported here]) at baseline, week 12, and month 12 for P4, and at baseline, weeks 4 and 12, and months 6, 9, and 12 for E2 and E1. In a phase 1 study, pharmacokinetic parameters were assessed after 7 daily doses of oral E2 mg/P4 mg (1/100 and 0.5/100). Results: In REPLENISH (n = 1, 835), mean P4 levels were 0.39 to 0.55 ng/mL with 100-mg P4 doses; E2 levels were 42.3 to 45.6 pg/mL and 23.0 to 27.4 pg/mL for the 1-mg and 0.5-mg E2 doses, respectively; E1 levels were 214 to 242 pg/mL and 114 to 129 pg/mL for the 1-mg and 0.5-mg E2 doses. In the phase 1 study (n = 40; day 7), mean C avg for P4 was 0.66 ng/mL with 100-mg P4 doses; E2 was 38.1 pg/mL and 29.2 pg/mL for 1 mg and 0.5 mg E2, respectively; and E1 was 211 and 106 pg/mL for 1 mg and 0.5 mg E2. All three analytes reached steady state within 7 days; accumulation ratios were 1.36 to 1.94. Conclusions: P4 levels observed with TX-001HR were similar in the phase 1 and 3 studies, and were associated with no endometrial hyperplasia with either E2 daily dose over 1 year in the REPLENISH phase 3 study, which showed significant improvements in menopausal vasomotor symptoms.